A natural PCID2-Targeting compound suppresses hepatocellular carcinoma progression: evidence from structure-based discovery and biological evaluation - Yuemaierjiang, Zebanuer; Sun, Jingjing; Song, Jiamin; Huang, Jiaping; Zhang, Huiyu; Xi, Lili; Guo, Jingjing; Luo, Xinyi (Frontiers in Pharmacology, 2025)
IntroductionHepatocellular carcinoma (HCC) is a highly aggressive malignancy with limited therapeutic options and poor prognosis, highlighting the urgent need for novel targets and effective agents. PCID2 (PCI-domain containing protein 2) has recently been recognized as a potential therapeutic target; however, specific inhibitors remain unidentified. Natural products, particularly monomeric compounds derived from traditional Chinese medicine (TCM), provide an important source for novel anticancer candidates.MethodsA molecular docking-based virtual screening of TCM-derived compounds were used to identify small molecules targeting PCID2. The binding interaction between the top candidate, 1,2,3,4,6-Penta-O-galloyl-β-D-glucose (β-PGG), and PCID2 was validated using surface plasmon resonance (SPR). The cytotoxicity and effects of β-PGG on HCC cell proliferation, migration, invasion, apoptosis, and cell cycle progression were evaluated in vitro. Exploratory analysis related to mechanisms were performed via Western blotting.Resultsβ-PGG was identified as a promising PCID2-targeting compound by molecular docking, and SPR confirmed its direct binding to PCID2. β-PGG significantly reduced HCC cell proliferation, migration, and invasion, while inducing apoptosis and cell cycle arrest. Treatment with β-PGG impeded the G0/G1 or S phase to G2/M phase. Mechanistically, β-PGG decreased PCID2 expression and downregulated Cyclin D1 and CDK6. At higher concentrations, β-PGG also suppressed PI3K and Akt phosphorylation.Discussionβ-PGG exhibits potent anti-HCC activity by modulating PCID2 expression, PI3K/Akt signaling, and cell cycle regulation, and it represents a promising lead compound with PCID2-targeting potential. This study not only support a rationale for further exploration of PCID2 as a therapeutic target in HCC but also provide valuable insights into the discovery of novel lead compounds from TCM for liver cancer treatment.